Defusing Genre through Generic Interplay:: Armand Ruffo’s Grey Owl: The Mystery of Archie Belaney as a Long Poem - Lapierre, Maude (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (University of New Brunswick, Dept. of English, 2012)
While critics of Armand Ruffo’s Grey Owl: The Mystery of Archie Belaney usually focus on the relationship between it and other biographical works on Belaney, there has also been some disagreement about the poem’s genre. Genre plays a crucial role in this text; Ruffo simultaneously supplements and opposes historical definitions of the Canadian long poem. The interweaving of epic, documentary, metafictional, and lyric forms, along with the decision to incorporate indigenous voices in Belaney/Grey Owl’s story, creates a contradictory subject and narrative, despite the fact that this long poem seems linear and chronological. By continuously shifting modes, Ruffo resists the historic desire to resolve Belaney/Grey Owl’s identity and instead fragments the unified subject that biographies seek to create. Through generic interplay, Ruffo develops a non-coercive way to deploy the Canadian long poem while simultaneously correcting some of the erasures that have marked its critical history. In this reading, tensions between fact and fiction are foregrounded and left to generate the contradictory subject that is Ruffo’s recreation of Grey Owl.